Exercise Training Stabilizes RyR2-Dependent Ca2+ Release in Post-infarction Heart Failure - Danielsen, Tore Kristian; Sadredini, Mani; Manotheepan, Ravinea; Aronsen, Jan Magnus; Frisk, Michael; Hansen, Marie Haugsten; Andressen, Kjetil Wessel; Hougen, Karina; Levy, Finn Olav; Louch, William E.; Sejersted, Ole Mathias; Sjaastad, Ivar; et al. (Frontiers in Cardiovascular Medicine, 2021)
Aim: Dysfunction of the cardiac ryanodine receptor (RyR2) is an almost ubiquitous finding in animal models of heart failure (HF) and results in abnormal Ca2+ release in cardiomyocytes that contributes to contractile impairment and arrhythmias. We tested whether exercise training (ET), as recommended by current guidelines, had the potential to stabilize RyR2-dependent Ca2+ release in rats with post-myocardial infarction HF. Materials and Methods: We subjected male Wistar rats to left coronary artery ligation or sham operations. After 1 week, animals were characterized by echocardiography and randomized to high-intensity interval ET on treadmills or to sedentary behavior (SED). Running speed was adjusted based on a weekly VO2max test. We repeated echocardiography after 5 weeks of ET and harvested left ventricular cardiomyocytes for analysis of RyR2-dependent systolic and spontaneous Ca2+ release. Phosphoproteins were analyzed by Western blotting, and beta-adrenoceptor density was quantified by radioligand binding. Results: ET increased VO2max in HF-ET rats to 127% of HF-SED (P < 0.05). This coincided with attenuated spontaneous SR Ca2+ release in left ventricular cardiomyocytes from HF-ET but also reduced Ca2+ transient amplitude and slowed Ca2+ reuptake during adrenoceptor activation. However, ventricular diameter and fractional shortening were unaffected by ET. Analysis of Ca2+ homeostasis and major proteins involved in the regulation of SR Ca2+ release and reuptake could not explain the attenuated spontaneous SR Ca2+ release or reduced Ca2+ transient amplitude. Importantly, measurements of beta-adrenoceptors showed a normalization of beta1-adrenoceptor density and beta1:beta2-adrenoceptor ratio in HF-ET. Conclusion: ET increased aerobic capacity in post-myocardial infarction HF rats and stabilized RyR2-dependent Ca2+ release. Our data show that these effects of ET can be gained without major alterations in SR Ca2+ regulatory proteins and indicate that future studies should include upstream parts of the sympathetic signaling pathway.